2014
DOI: 10.1128/iai.00071-14
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Signal-Regulated Protein Kinase Mediates Interleukin 17 (IL-17)-Induced IL-8 Secretion in Helicobacter pylori-Infected Human Gastric Epithelial Cells

Abstract: During preparation of figures showing the results of Western blots, the following bands from control samples were inadvertently duplicated:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Firstly, Luzza et al reported that increased production of active IL-17A during H. pylori infection may play an important role in the inflammatory response to H. pylori colonization [16]. Thereafter, several studies revealed that IL-17, a key regulator of neutrophil chemotaxis, is produced in excess in H pylori-infected stomachs [17,23]. These results suggest that IL-17A may contribute to H. pylori-induced gastric inflammation.…”
Section: Discussionmentioning
confidence: 91%
“…Firstly, Luzza et al reported that increased production of active IL-17A during H. pylori infection may play an important role in the inflammatory response to H. pylori colonization [16]. Thereafter, several studies revealed that IL-17, a key regulator of neutrophil chemotaxis, is produced in excess in H pylori-infected stomachs [17,23]. These results suggest that IL-17A may contribute to H. pylori-induced gastric inflammation.…”
Section: Discussionmentioning
confidence: 91%
“…Pathway analysis demonstrates that CCL8 and IL‐8 are both involved in the ERK 1/2 signaling pathway. ERK 1/2 are protein kinases, ERK1 and ERK2 belonging to one of the three major mitogen‐activated protein kinase (MAPK) families (Sebkova et al ., ). IL‐8 induction is transcriptionally controlled through multiple promoter elements, and MAPK signaling pathways are associated with inflammatory stimuli that regulate IL‐8 production (Dong et al ., ; Hoffmann et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…IL‐17 family cytokines per se do not possess chemotactic activity (Zou and Restifo, ) but instead trigger cell‐mediated immune responses by inducing secretion of unrelated cytokines and chemokines. Following H. pylori infection IL‐17A induces secretion of IL‐8, by activation of the ERK 1/2 MAP kinase cascade (Sebkova et al ., ; Kabir, ). IL‐17 may therefore indirectly promote cell‐mediated immunity, in part, by triggering release of IL‐8, a potent chemoattractant for neutrophils.…”
Section: H Pylori Stat3 and Il‐17mentioning
confidence: 99%